Cavernous Hemangioma-Like Kaposi Sarcoma: Histomorphologic Features and Differential Diagnosis. (25th September 2013) - Onak Kandemir, Nilüfer; Barut, Figen; Doğan Gün, Banu; Solak Tekin, Nilgün; Hallaç Keser, Sevinç; Oğuz Özdamar, Şükrü
Abstract : Aim . Cavernous hemangioma-like Kaposi sarcoma is a rare morphologic type of Kaposi sarcoma. So far there are no cases in the literature defining the histological features of this morphologic spectrum in detail. In this study we presented two classical-type cutaneous Kaposi sarcoma cases with histologic findings resembling cavernous hemangioma in company with clinical and histopathological data. Cases . One hundred and eighty-five classical-type cutaneous Kaposi sarcoma lesions in 79 patients were assessed retrospectively in terms of histopathological features. Findings of two cases showing features of cavernous hemangioma-like Kaposi sarcoma whose clinical data could be accessed were presented in accompany with the literature data. Both cases were detected to have bluish-purple, protruded, irregularly bordered cutaneous lesions. Histopathological examination revealed a lesion formed by cavernous hemangioma-like vascular structures organized in a lobular pattern that became dilated and filled with blood. Typical histological findings of early-stage KS, consisting of mononuclear inflammation, extravasated erythrocytes, and a few immature vascular structures in superficial dermis, were observed. All cases were serologically HIV-1 negative. A positive reaction with HHV-8, CD31, CD34, and D2-40 monoclonal antibodies was identified at both cavernous hemangioma-like areas and in immature vascular structures. Results . Cavernous hemangioma-like Kaposi sarcoma is a rare Kaposi sarcoma variant presenting with diagnostic challenges, that may be confused with hemangioma. As characteristic morphological features may not be observed in every case, it is important for diagnostic purposes to show immunohistochemical HHV-8 positivity in this variant.